MENGENAL METODE ISTINBATH HUKUM MAJELIS TARJIH MUHAMMADIYAH - Fikri, Yudistia Teguh Ali; Gopar, Ida Abdul; Faatinisa, Esty; Dachlan, Mochamad Faizal Almaududi Azis (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2022)
This article introduces the legal istinbath method of the tarjih muhammadiyah council. The tarjih council was born in the decision of the Pekalongan congress in 1927 the function to consider and resolve all problems that arise is debated by Muhammadiyah people to know the opinion chosen because it is bold and its postulates based on the Qur'an and As-Sunnah. This article aims to find out how the istinbath method used by Muhammadiyah in establishing law, using a qualitative approach, by adding data from secondary data sources, previous research, or existing data in organizations or agencies. The istinbath tarjih muhammadiyah method is based on the Al-Quran and As-Sunnah, The ijtihad method with Bayani, Burhani, and Irfani Muhammadiyah approaches solves problems that occur in society.Keywords: Istinbath, Islamic Law, Tarjih Council, Muhammadiyah